Re-Infection Outcomes Following One- And Two-Stage Surgical Revision of Infected Knee Prosthesis: A Systematic Review and Meta-Analysis. - Setor K Kunutsor; Michael R Whitehouse; Erik Lenguerrand; Ashley W Blom; Andrew D Beswick; INFORM Team (PLoS ONE, 2016)
Background Periprosthetic joint infection (PJI) is a serious complication of total knee arthroplasty. Two-stage revision is the most widely used technique and considered as the most effective for treating periprosthetic knee infection. The one-stage revision strategy is an emerging alternative option, however, its performance in comparison to the two-stage strategy is unclear. We therefore sought to ask if there was a difference in re-infection rates and other clinical outcomes when comparing the one-stage to the two-stage revision strategy. Objective Our first objective was to compare re-infection (new and recurrent infections) rates for one- and two-stage revision surgery for periprosthetic knee infection. Our second objective was to compare between the two revision strategies, clinical outcomes as measured by postoperative Knee Society Knee score, Knee Society Function score, Hospital for Special Surgery knee score, WOMAC score, and range of motion. Design Systematic review and meta-analysis. Data sources MEDLINE, EMBASE, Web of Science, Cochrane Library, reference lists of relevant studies to August 2015, and correspondence with investigators. Study selection Longitudinal (prospective or retrospective cohort) studies conducted in generally unselected patients with periprosthetic knee infection treated exclusively by one- or two-stage revision and with re-infection outcomes reported within two years of revision surgery. No clinical trials comparing both revision strategies were identified. Review methods Two independent investigators extracted data and discrepancies were resolved by consensus with a third investigator. Re-infection rates from 10 one-stage studies (423 participants) and 108 two-stage studies (5,129 participants) were meta-analysed using random-effect models after arcsine transformation. Results The rate (95% confidence intervals) of re-infection was 7.6% (3.4-13.1) in one-stage studies. The corresponding re-infection rate for two-stage revision was 8.8% (7.2-10.6). In subgroup analyses, re-infection rates remained generally similar for several study-level and clinically relevant characteristics. Postoperative clinical outcomes of knee scores and range of motion were similar for both revision strategies. Limitations Potential bias owing to the limited number of one-stage revision studies and inability to explore heterogeneity in greater detail. Conclusions Available evidence from aggregate published data suggest the one-stage revision strategy may be as effective as the two-stage revision strategy in treating infected knee prostheses in generally unselected patients. Further investigation is warranted. Systematic review registration PROSPERO 2015: CRD42015017327.